Dialectic Second language acquisition and optimal learning age - Amayreh, Muhammad Ismail (Journal of Humanities & Social Sciences, 2021)
The issue of language education is one of the most delicate human issues. It is very relevant to the social and political history of society and is also one of the issues imposed by human reality. It is also one of the issues that has intensified the differences between linguists and psychologists in the ways of acquiring them.Perhaps there are things that stand in front of the acquisition of the second language, language is not a neutral system or a tool to be used in a timely manner or in a generation and that’s it, but is a language with its luster and heritage and attractiveness, what are the factors that stand in front of the acquisition of the second language? Is there a real conflict between languages ​​affecting the acquisition of language in children? What are the most important stages of growth in children and their relation to linguistic development?In fact, there is a difference between mother tongue, second language and foreign language, differentiating between these concepts will make it easier for us to reach the appropriate age to acquire the language. The reason is that the acquisition or learning of any language stems from the goals related to the life of the individual, whether professional, economic or social. The bilingual issue raises an important question: Are the two linguistic systems of the human brain separate or connected?
Keywords: language acquisition; foreign language; appropriate age